Bibliometric analysis on the international publication of muslim brotherhood - Iqbal Rasyad; Gonda Yumitro (Komunitas Ilmuwan dan Profesional Muslim Indonesia (KIPMI), 2023)
This article analyzes the trend of international publications related to the Muslim Brotherhood using the Scopus database. This study aims to determine the publication trends by region, subject area of publication, type of publication, number of documents for each author, and number of papers for each university. The data collected by the authors were taken from the search results in the Scopus database with a combination of the keywords